Surface processes at a polymetallic (Mn-Fe-Pb) sulfide subject to cyanide leaching under sonication conditions and with an alkaline pretreatment: Understanding differences in silver extraction with X-ray photoelectron spectroscopy (XPS) - Larrabure, G. (2021)
Leaching of polymetallic sulfides is often challenging due to the complexity of these systems. The main issues are related to the formation of surface by-products or to the presence of different metals that require a greater consumption of chemicals compared to that needed to extract the target metal during leaching. This latter case is followed in the present work using X-ray photoelectron spectroscopy (XPS) during the leaching of a silver-containing polymetallic (Mn-Fe-Pb) sulfide under three different cyanidation procedures: (1) conventional leaching, (2) ultrasound-assisted leaching, and (3) leaching of a sample pretreated in alkaline media. In all cases, leaching results in the build-up of Pb compounds (oxides/hydroxides) on the surface of the minerals, suggesting a mechanism in which Pb is first leached by hydroxide and cyanide and later is re-adsorbed as an external layer on the minerals. On the other hand, the effect of each process on Mn was quite distinct: 1) Conventional leaching leads to the oxidation of the sulfide (pyrite) surface and a slight increase of surface Mn species; 2) Ultrasound-assisted leaching decreases surface Mn by dissolving oxidized species, which exposes fresh sulfide surfaces and increases Ag extraction; and 3) An alkaline pretreatment at high temperature exposed fresh sulfide surfaces and decreased the surface concentration of Mn. The fact that ultrasound-assisted leaching and leaching after an alkaline pretreatment allow for a higher Ag extraction (60% and 75% of total Ag, respectively, as opposed to the 25% extracted via conventional leaching), indicates that leaching is more efficient if the surface is not oxidized and if Mn is removed from the samples, either before or during leaching. © 2020 Elsevier B.V.